New insights into Aspergillus guangdongensis (Aspergillaceae) and its first global record since the original description - Wei, Yu-Hui; Liou, Guey-Yuh; Tzean, Shean-Shong; Hsieh, Sung-Yuan (Phytotaxa, 2023)
Aspergillus guangdongensis was included in the Aspergillus section Ochraceorosei. A notable feature of this section is that the majority of the described species are recognized only from the type strain. A. guangdongensis accommodates only a single strain, and the intraspecific variation within this species has not been realized. In investigating fungi from soil and stored plant seeds, two isolates, namely, BCRC 32544 and BCRC 32546, were identified as A. guangdongensis newly recorded from Taiwan. This is the first global record since its original description. To the best of our knowledge, all known species of section Ochraceorosei have not been previously reported in Taiwan. Our study also involved the phylogenetic analyses based on four loci genes (ITS, BenA, CaM, and RPB2), as well as a comparison of cultural and morphological characteristics between strains of A. guangdongensis and among closely related species, revealing obvious intraspecific variability. Aspergillus spp. produce a diverse array of important secondary metabolites, which have motivated great interests in scientific research groups. Therefore, a brief summary of research articles on the metabolites produced by the related species within the series Funiculosi under the Aspergillus section Ochraceorosei have been presented in this study.